Risk assessment of bronchopulmonary pathology in the workers of coal and asbestos processing industries based on a hygienic assessment of the conditions of work and the results of clinical-and-genealogical study - Cherniuk, V.I.; Andrushchenko, T.A.; Soloviov, A.I.; Goncharov, A.E. (Environment & Health, 2019)
Introduction: When establishing the causal relationship of the development of bronchopulmonary pathology with the conditions of work in the workers of main professions in coal and asbestos processing industries, a role of burdened hereditary has not been fully established yet. In particular, can burdened hereditary for bronchopulmonary pathology be a common cause or risk factor for the occurrence of the occupational diseases of respiratory system?Objective: We found out the dependence of the development of bronchopulmonary pathology among the workers of coal and asbestos processing industries from the influence of the conditions of work and the presence of burdened hereditary susceptibility to respiratory system diseases.Materials and methods: We applied informative-and-analytical methods: the study of sanitary-and-hygienic characteristics of the conditions of work, materials of the preliminary scientific reports; clinical-and-genealogical research (compilation and analysis of 215 pedigrees).Results: The causal relationship of the bronchopulmonary pathology with the working conditions of workers in the main professions of the coal and asbestos processing industry has been established. A lower limit of the relative risk (RR) of 1.69 and an upper one of 1.76 units are in compliance with an average risk of the development of bronchopulmonary pathology with an aetiological share of the factor of the conditions of work EF (1) of 41–43%. It was found that in the families with burdened heredity of bronchopulmonary pathology, the risk of its development is two times higher than in the control group (FA = 2.1, P≤0.001; χ² = 16.75). Estimation of the aetiological share of the risk of the influence of burdened heredity in the families of the respondents in the EF study (2) indicates a significant (from 47 to 48%) share of the contribution of this factor to the development of bronchopulmonary pathology. In the families where burdened heredity of the respiratory system and professional succession were observed simultaneously, the risk of the development was 1.5 times higher in comparison with the families where there was no burdened history of respiratory system diseases and professional succession (FA = 1.5; P≤0.01 ; χ² = 5.65).Conclusions: A relatively low risk of the development of bronchopulmonary pathology in analyzed sample can be explained by the existence of other risk factors or a common cause, or features of a non-random selection into the control group.The obtained coefficients of the family aggregation indicate that in the families with burdened heredity of bronchopulmonary pathology and occupational succession, a risk of the development of this pathology is higher in comparison with the families without positive family cases of respiratory system diseases.
Keywords: bronchopulmonary pathology; risk assessment; hygienic assessment of the conditions of work; clinical-and-genealogical analysis